2013
DOI: 10.4038/cjsbs.v41i2.5385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Pretreatments on the Quality of Minimally Processed Pineapple Stored in Polystyrene Packages

Abstract: Minimally processed pineapple (Ananas comosus L.) cv. Mauritius stored at cold temperature for seven days were evaluated for physicochemical, sensory and microbiological qualities. Pineapple pieces were treated with 1% sodium chloride, 1% calcium chloride, a combination of 1% sodium chloride and calcium chloride, 1% ascorbic acid, 1% citric acid, 0.1% chitosan and distilled water (control) and packed in polystyrene packages before storage. Pretreatments did not significantly affect the physicochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Both ascorbic and citric acid inhibit the growth of yeasts and moulds by lowering the pH of processed commodity. Similarly, Ediriweera et al, (2012) reported zero yeast and mould counts for fresh cut bell pepper, treated with 1% sodium chloride and stored at 5-7 0 C by day 7. When sodium chloride is incorporated as a pre-treatment, high osmotic pressure results in plasmolysis of microbial cells causing dehydration and inhibition of growth of microorganisms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Both ascorbic and citric acid inhibit the growth of yeasts and moulds by lowering the pH of processed commodity. Similarly, Ediriweera et al, (2012) reported zero yeast and mould counts for fresh cut bell pepper, treated with 1% sodium chloride and stored at 5-7 0 C by day 7. When sodium chloride is incorporated as a pre-treatment, high osmotic pressure results in plasmolysis of microbial cells causing dehydration and inhibition of growth of microorganisms.…”
Section: Discussionmentioning
confidence: 89%
“…During preparation of fresh cuts, produce are immersed in pre-treatment solutions at the final stage of handling operations. Compounds such as ascorbic acid, citric acid, sodium metabisulphite, sodium chloride and calcium chloride have been utilized throughout the world as suitable preservatives to manage microbial problems and reduce browning for maintaining quality of fresh cuts such as potato, apple (Ahvenainen, 1996), bell pepper (Ediriweera et al, 2012), Pineapple plus amberella (Daranagama et al, 2012), Ela Batu (Solanum surattense) (Dharmabandu et al, 2007) and Jak fruit (Latifah et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Samples dipped in distilled water were used as the control. Treated samples were allowed to drip dry for 15 min (Dharmabandu et al 2007;Ediriweera et al 2012). Five to seven (5-7) slices of pre-treated commodity were aseptically transferred to polystyrene packages of 70 g capacity.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Potato Dextrose Agar is recommended by the American Public Health Association for the enumeration of yeasts and moulds in examination of dairy products, soft drinks, dried and frozen foods and other types of product. The yeast and mould count was done by following the method described by Ediriweera et al (2012). A 10 -2 dilution of the sample was prepared by serial decimal dilution.…”
Section: Microbial Analysis Yeast and Mould Countmentioning
confidence: 99%